Tantangan Identitas Nasional dalam Perspektif Pancasila di Tengah Arus Globalisasi - Gusniyanda, Elsa Maharani; Amanda, Aura Fricila; Andriyani, Rika; Azzahra, Dinnie; Rahmadini, Suci Riska (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the challenges of Indonesia's national identity from the perspective of Pancasila amidst the waves of globalization. Globalization brings significant impacts to various aspects of life, including culture, social, economic, and political factors, which can affect the preservation of national identity. The method used in this research is a literature review, in which the author collects, analyzes, and synthesizes the results of previous relevant studies. The discussion of this study focuses on the role of Pancasila as the foundation of the state in preserving the integrity of national identity in the face of globalization, with emphasis on values such as tolerance, humanity, and unity. The research findings show that strengthening national identity through civic education and the preservation of local culture is essential in addressing the challenges of globalization. Pancasila functions as a moral guideline that can adapt to the times without losing its essence.